Properties of Insulation-Type Green Composite Panels Manufactured from Recycled Cardboard - Mazaherifar, Mohammad Hassan; Hiziroglu, Salim; Brenci, Luminita Maria; Cosereanu, Camelia (Applied Science-Basel, 2025)
This study investigates the influence of two processing methods, namely wet and dry, on the structural, physical, mechanical, and acoustic performance of green lignocellulosic fiber-based composite panels. A comprehensive evaluation was carried out to compare the vertical density profile, affinity to water, thermal insulation and sound absorption, microstructural features, and mechanical performance of two types of experimental panels. The dry-processed samples exhibited 24% more prominent vertical density profile and superior dimensional stability, with lower thickness swelling (TS) and water absorption (WA) due to their more compact fiber arrangement compared to those of the specimens made using the wet process. However, the wet-processed panel demonstrated significantly enhanced mechanical properties, including 36% higher modulus of elasticity (MOE), 61% modulus of rupture (MOR), and 67% internal bonding strength (IB). Such findings could be attributed to their increased fibrillation and improved inter-fiber bonding compared with those of the panels made using the dry process. The thermal conductivity values of the wet- and dry-processed panels were found to be 0.053 W/mK and 0.057 W/mK, respectively. Acoustic analysis of the samples revealed that while the dry-processed panel slightly outperformed in terms of low-frequency sound absorption, the wet-processed panel exhibited superior high-frequency absorption, particularly when perforations were introduced. Microscopic examination of the samples confirmed that wet processing produced a more homogenous and fibrillated microstructure, correlating well with the observed enhancements in mechanical and acoustic performance. In conclusion, it can be stated that the processing strategies of such panels could be applied for diverse engineering applications, including thermal insulation, acoustic damping, and sustainable structural materials.
Keywords: recycled cardboard; green composite panels; lignocellulosic fiber; acoustic absorption behavior; mechanical properties